Mechanically stable VPO catalyst and preparation method thereof
By adding ZnO to the VPO catalyst and preparing a catalyst in the form of a mold, the problem of insufficient reaction activity and mechanical stability of the existing VPO catalyst in the butan oxidation to maleic anhydride reaction is solved, and the performance and cost reduction of the catalyst are improved.
Patent Information
- Application Number
- CN202380065757.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-21
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
Existing VPO catalysts have low inherent reactive activity and mechanical stability in the reaction of butan oxidation to maleic anhydride, resulting in the need of a large number of catalysts and high cost.
By adding ZnO to the VPO catalyst, a VPO catalyst in the form of a shaped body is formed, which improves its mechanical stability and catalytic performance. The catalyst preparation method includes providing a reaction mixture, performing partial reduction of the V(V) compound, filtering and drying the intermediate product, adding ZnO and forming into particles, and subsequent activation in a specific gas mixture.
The mechanical stability and catalytic performance of VPO catalysts are improved, reducing the amount and cost of catalysts used, while maintaining the porosity and catalytic performance of the catalysts.
Smart Images

Figure CN119866247A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a VPO catalyst in the form of a shaped body for the oxidation of hydrocarbons with molecular oxygen, in particular for the oxidation of butane with molecular oxygen to maleic anhydride, characterized in that the VPO catalyst contains ZnO. Such a VPO catalyst has an increased mechanical stability.
[0002] The present invention further relates to a method for preparing the VPO catalyst of the present invention, said method comprising the following steps:
[0003] a) providing a reaction mixture comprising a V(V) compound, a P(V) compound, optionally a Mo compound, a reducing agent and a solvent,
[0004] b) reducing said V(V) compound at least partially to vanadium hydrogen phosphate with said reducing agent so as to obtain an intermediate product suspension,
[0005] c) filtering the intermediate product suspension from step b) in order to obtain an intermediate product,
[0006] d) drying and / or calcining the intermediate product at a temperature of up to 300° C. in order to obtain a dried intermediate product,
[0007] d 1 ) optionally mixing the dried intermediate product with graphite and / or 2 ) compacting or granulating the dried intermediate product,
[0008] e) the product from step d) or d) 1 ) and / or d 2 ) is formed into particles,
[0009] f) activating the particles at a temperature above 200° C. in a gas mixture formed from nitrogen, hydrogen and water vapor,
[0010] Characterized in that ZnO is added after step c) but before step f).
[0011] The invention further relates to the use of ZnO for stabilizing VPO catalysts in the form of shaped bodies or the use of ZnO as a binder for VPO catalysts in the form of shaped bodies. Background Art
[0012] Maleic anhydride is a chemical intermediate of great economic importance. It is used, for example, alone or in combination with other acids in the preparation of alkyd resins and polyester resins. In addition, maleic anhydride is also an intermediate that can be used flexibly for chemical synthesis, for example for the synthesis of gamma-butyrolactone, tetrahydrofuran and 1,4-butanediol, which themselves can in turn be used as solvents or can be further processed into polymers such as polytetrahydrofuran or polyvinylpyrrolidone.
[0013] The preparation of maleic anhydride is generally carried out by partial oxidation of n-butane in the gas phase with molecular oxygen or with a gas comprising molecular oxygen in the presence of a vanadium-phosphorus-oxygen catalyst (VPO catalyst) comprising vanadium pyrophosphate (VPP). Vanadium pyrophosphate has a valence of +4 for vanadium and is particularly suitable for the preparation of maleic anhydride from unbranched saturated or unsaturated hydrocarbons having at least four carbon atoms. Both fixed bed reactors and fluidized bed reactors can be used.
[0014] VPO catalysts have only a low intrinsic reactivity in the reaction of n-butane to form maleic anhydride. Therefore, in order to obtain sufficient conversions, large amounts of catalysts are required. It should also be noted in the case of VPO catalysts that they are completely among the most expensive non-precious metal catalysts, largely due to the high cost of their starting materials. Therefore, the following object is proposed, namely to improve the catalyst performance (activity and selectivity) or also to improve the service life and mechanical stability of such catalysts. It is known from the prior art that the performance of VPO catalysts can be improved by incorporating foreign elements into the vanadium-phosphorus-oxygen phase (VPO phase), for example by incorporating molybdenum (Mo promoter or Mo dopant).
[0015] US 5,929,256 discloses the synthesis of an active vanadium-phosphorus catalyst modified with molybdenum for the preparation of maleic anhydride. A compound containing a major portion of pentavalent vanadium is reacted with a compound containing pentavalent phosphorus in an alcohol medium suitable for reducing vanadium to an oxidation valence of less than 5. Platinum is inserted into the reaction product, wherein a solid, molybdenum-modified precursor composition is formed. The alcohol is removed in order to obtain a dried, solid, molybdenum-modified precursor composition. A shaped body comprising a dried, solid, molybdenum-modified precursor compound is formed. The dried and shaped molybdenum-modified precursor composition is activated in order to convert it into an active catalyst.
[0016] US 5,070,060 discloses an improvement in an oxidation catalyst for partial oxidation of n-butane comprising a mixed oxide of vanadium and phosphorus, a mixed oxide of zinc and lithium, the improvement comprising adding a molybdenum compound modifier to the catalyst during the reaction of a reduced vanadium compound with concentrated phosphoric acid in an amount of about 0.005 to 0.025 / 1 Mo / V. The addition of Mo results in a catalyst that is very stable, forms a more active system and can be stored longer than the unmodified catalyst.
[0017] US 3,980,585 discloses a catalyst composite suitable for converting normal C 4 Hydrocarbons are converted into maleic anhydride, the catalyst composite comprising the components vanadium, phosphorus and copper and one of the elements selected from the group consisting of Te, Zr, Ni, Ce, W, Pd, Ag, Mn, Cr, Zn, Mo, Re, Sm, La, Hf, Ta, Th, Co, U and Sn, preferably with an alkali metal or alkaline earth metal.
[0018] US 4,056,487 discloses a catalyst which is suitable for the partial oxidation of alkanes to the corresponding anhydrides, for example, the conversion of normal C 4 The conversion of hydrocarbons into maleic anhydride comprises the components vanadium, phosphorus and oxygen, Nb, Cu, Mo, Ni, Co and Cr. Preference is given to compositions which additionally comprise one or more elements from Ce, Nd, Ba, Hf, U, Ru, Re, Li or Mg.
[0019] US 4,515,904 discloses a process for preparing a phosphorus-vanadium catalyst and a phosphorus-vanadium metal co-catalyst for use in the preparation of maleic anhydride from butane, wherein the process comprises: reacting a vanadium compound with a phosphorus halide in an organic ether solvent having about 2 to 10 carbon atoms at a temperature of about 0°C to about 200°C in the presence of water or an aliphatic alcohol having about 1 to about 8 carbon atoms; removing the solvent; and activating the catalyst by adding butane or another hydrocarbon starting product and a phosphorus compound at a temperature of about 300°C to about 500°C.
[0020] US 5,158,923 discloses an improvement in an oxidation catalyst for partial oxidation of n-butane comprising a mixed oxide of vanadium and phosphorus, a mixed oxide of zinc and lithium, which improvement comprises adding a molybdenum compound modifier to the catalyst during the decomposition of reduced vanadium compounds with concentrated phosphoric acid in an amount of about 0.005 to 0.025 / 1 Mo / V. The addition of Mo results in a catalyst that is very stable, forms a more active system and can be stored longer than the unmodified catalyst.
[0021] US 5,262,548 discloses an improvement in an oxidation catalyst for partial oxidation of n-butane comprising a mixed oxide of vanadium and phosphorus, a mixed oxide of zinc and lithium, the improvement comprising adding a molybdenum compound modifier to the catalyst during decomposition of reduced vanadium compounds with concentrated phosphoric acid in an amount of about 0.005 to 0.025 / 1 Mo / V. The addition of Mo results in a catalyst which forms a stable active system and has a longer service life than the unmodified catalyst.
[0022] WO 2013062919 A1 discloses a method for preparing an enhanced VPO catalyst, wherein the catalyst comprises a mixed oxide of vanadium and phosphorus and wherein the catalyst is enhanced with at least one from niobium, cobalt, iron, zinc, molybdenum or titanium, wherein the method comprises the steps of: (i) preparing a VPO catalyst comprising vanadium pyrophosphate as a main component and containing less than 5 wt% of vanadium phosphate, (ii) contacting the VPO catalyst with a solution comprising a compound having at least one metal selected from the group consisting of niobium, cobalt, iron, zinc, molybdenum or titanium as a metal source to form a metal-impregnated VPO catalyst, and (iii) drying the metal-impregnated VPO catalyst to form an enhanced VPO catalyst. In one embodiment, a niobium-activated VPO catalyst is prepared.
[0023] US 5,280,003 discloses an improvement in an oxidation catalyst for partial oxidation of n-butane comprising vanadium and mixed oxides of phosphorus, zinc, lithium and molybdenum, the improvement comprising carrying out its preparation while carrying out the crystallization step under static conditions which allow more uniform conditions for crystal growth. The static conditions are maintained by heating the solvent under reflux during the crystallization period.
[0024] US 4,251,390 discloses an improved oxidation catalyst for partial oxidation of n-butane, comprising a vanadium and phosphorus mixed oxide, characterized in that a zinc compound is added to the catalyst in an amount of 0.15 to 0.001 Zn / V during the reaction of the reduced vanadium moiety with concentrated phosphoric acid. The addition of zinc produces a catalyst which is easily activated and very stable to rising temperatures of the reaction system. Small amounts of lithium compounds and silicon compounds also have an additional desired catalytic effect without reducing the advantages of the zinc compound.
[0025] DE 10 2014 004786 A1 relates to a catalyst comprising vanadium-phosphorus oxide and an alkali metal, wherein the weight proportion of the alkali metal in the vanadium-phosphorus oxide is in the range of 10 to 400 ppm relative to the total weight of the vanadium-phosphorus oxide, and also to a method for its preparation and the use of the catalyst for gas-phase oxidation of hydrocarbons, in particular for preparing maleic anhydride.
[0026] CN 101036891 A discloses a method for regenerating a fluidized bed catalyst for oxidizing n-butane to maleic anhydride, comprising the following steps: preparing a precursor matrix powder and auxiliary materials; mixing the catalyst ash captured by a fluidized bed device with the prepared precursor matrix powder and auxiliary materials; adding a water-soluble resin binder and stirring under aqueous temperature control conditions; and finally forming by spray drying to obtain a regenerated catalyst. The regenerated catalyst of the invention can supplement or replace the crude catalyst in the fluidized bed reactor and is equivalent to the crude catalyst in terms of activity, particle size and use.
[0027] CN 1282631 A discloses a vanadium-phosphorus oxide catalyst, which is characterized by adding zirconium, molybdenum and zinc and having an atomic ratio between vanadium:phosphorus:zirconium:molybdenum:zinc of 1.0:1.0-1.5:0.02-0.06:0.02-0.06:0.02-0.06. In addition, a method for preparing the vanadium-phosphorus oxide catalyst is disclosed, characterized in that 6 parts by weight of vanadium pentoxide and 50-60 parts of concentrated hydrochloric acid are heated under reflux for 1-5 hours and then phosphoric acid is added. The amount added is designed to make the atomic ratio between vanadium and phosphorus between 1.0:1.0-1.5 and continue the reflux step for 1-5 hours. After cooling, a mixture formed by zirconium nitrate, ammonium dimolybdate and zinc acetate and 50-200 parts of water are added. Solution, zirconium nitrate, ammonium dimolybdate and zinc acetate are added so as to achieve an atomic ratio between vanadium:zirconium:molybdenum:zinc of 1.0:0.02-0.06:0.02-0.06:0.02-0.06, then the mixture is evaporated slowly and carefully in a water bath for 15-30 hours so as to obtain a viscous colloid, and the colloid is dried at 120° C. so as to obtain a dark green solid, which is the vanadium-phosphorus oxide catalyst of the invention.
[0028] CN 111701608 A discloses a method for preparing a vanadium-phosphorus-oxygen catalyst modified with hydrotalcite, the method comprising the following steps: preparing a vanadium-phosphorus-oxide precursor by mixing a vanadium source, benzyl alcohol and a C3 to C8 monohydric alcohol to obtain a mixture, then adding a phosphorus source, heating to 100° C. to 200° C., continuing the reaction, filtering the product and drying it to obtain a vanadium-phosphorus-oxygen precursor; preparing a hydrotalcite additive by dissolving a water-soluble inorganic zinc source, an inorganic magnesium source and an inorganic aluminum source in water, adding an alkali metal source, heating to 65° C. to 200° C., and then drying the product. The invention relates to a method for preparing a hydrotalcite-modified vanadium-phosphorus-oxygen catalyst. The method comprises reacting the vanadium-phosphorus-mixed oxide-oxygen catalyst with the inorganic zinc source, the inorganic magnesium source and the inorganic aluminum source, cooling and aging for 6 to 12 hours, filtering, washing, drying and calcining at a temperature between 350° C. and 550° C. to obtain a hydrotalcite additive, wherein the total amount of zinc and magnesium and the amount of aluminum in the inorganic zinc source, the inorganic magnesium source and the inorganic aluminum source is between 1 and 4:1, and the molar ratio between magnesium and zinc is between 1 and 5:10; mixing the hydrotalcite additive with a vanadium-phosphorus mixed oxide-oxygen precursor in a mass ratio of 1-10:100, heating to 300-500° C. and calcining to obtain a hydrotalcite-modified vanadium-phosphorus-oxygen catalyst.
[0029] CN 106938197 A discloses a method for preparing a vanadium-phosphorus-oxygen catalyst. The method comprises the following steps: preparing a vanadium hydrogen phosphate hemihydrate catalyst precursor powder doped with a metal auxiliary agent, wherein the metal auxiliary agent is at least one of Fe, Mo, Co, Ce, Zr, Nb and Ni, and the molar ratio of the metal auxiliary agent to vanadium is between 0.06 and 0.15; and mixing the catalyst precursor powder with a binder and an auxiliary material and continuously extruding or tableting to obtain a vanadium-phosphorus oxide catalyst, wherein the binder is at least one of phosphoric acid, pyrophosphoric acid, trimethyl phosphate, triethyl phosphate, aluminum dihydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, zinc phosphate, tricalcium phosphate, ammonium phosphate, ammonium pyrophosphate and ammonium hexametaphosphate, the auxiliary material is at least one of graphite, carbon nanotubes, graphene and carbon powder, and the mass ratio between the catalyst precursor powder, the binder and the auxiliary material is between 100:(0.1-15):(0.1-10). The preparation method of the vanadium-phosphorus oxide catalyst is simple and does not impose special requirements on production equipment, and the obtained catalyst has the advantages of high strength, good catalytic effect and easy industrial production and application.
[0030] To prepare a VPO catalyst containing a VPP phase, vanadium pentoxide (VPO) is usually reacted with phosphoric acid in an organic alcohol solvent and benzyl alcohol as a reducing agent. 2 O 5) is reduced, wherein in addition to benzaldehyde, vanadium hydrogen phosphate (VHP) is also produced. The redox reaction ("reduction") that takes place here is as follows, namely, vanadium with an oxidation valence of V (V(V)) reacts to form the VHP phase, wherein the substance species of vanadium (VO 2+ ) exists as vanadium (V(IV)) at oxidation valence IV:
[0031] (1)V 2 O 5 +2H 3 PO 4 +Ph-CH 2 -OH→2VOHPO 4 *1 / 2H 2 O+Ph-CHO+2H 2 O
[0032] In the subsequent activation step, the VHP phase is converted into the vanadium pyrophosphate phase by the action of heat while water is splitting.
[0033] (2)2VOHPO 4 *1 / 2H 2 O→(VO) 2 P 2 O 7 +1 1 / 2 H 2 O
[0034] The problem in the case of catalytic conversion of butane into maleic anhydride with a VPO catalyst is that the process must be carried out under a mechanism limited by pore diffusion. Then, the porosity directly affects the catalytic yield. Therefore, it must be noted that the pore structure is not negatively affected during shaping (for example, by tableting). But as a result, the mechanical stability of the shaped body is lost. However, the mechanical stability must be large enough to allow the sheet to withstand the filling process intact (falling into a reaction tube of about 6 meters in length). Otherwise, due to smaller fragments, the dynamic pressure in the process is too high, which leads to high compressor costs or reduced throughput. Therefore, the technical purpose is to improve the mechanical strength of the shaped body without negatively affecting the pore structure. Summary of the invention
[0035] It was therefore an object of the present invention to provide an improved VPO catalyst for the gas phase oxidation of hydrocarbons, in particular for the preparation of maleic anhydride, which has comparable porosity and catalytic properties compared to the catalysts customary hitherto and at the same time has significantly improved mechanical strength.
[0036] This object is achieved by a VPO catalyst in the form of a shaped body for the oxidation of hydrocarbons with molecular oxygen, in particular for the oxidation of butane with molecular oxygen to maleic anhydride, characterized in that the VPO catalyst comprises ZnO.
[0037] The VPO catalyst of the present invention comprises a VPO phase or consists of it or consists essentially of it. For example, relative to the total weight of the VPO catalyst, the VPO catalyst of the present invention comprises a VPO phase in an amount greater than 70 wt%, preferably greater than 80 wt%, more preferably greater than 90 wt%. In the remainder, the VPO catalyst may include VPP, dopants and unconverted oxides in the initial material, such as vanadium pentoxide or phosphorus oxide.
[0038] The VPO catalyst of the present invention may optionally comprise between 0.1 wt% and 1 wt%, preferably between 0.4 wt% and 0.7 wt% Mo, relative to the total weight of the VPO catalyst.
[0039] However, the VPO catalyst according to the invention may also contain alkali metals such as Na and / or K, preferably 80 to 300 ppm of alkali metals. In addition, the VPO catalyst according to the invention may also contain carbon, for example in the form of graphite, in an amount of, for example, 3% to 5% by weight, relative to the total weight of the catalyst. The graphite present is used, for example, as a tableting aid.
[0040] The VPO catalyst of the invention has ZnO (zinc(II) oxide), but other zinc compounds may also be present in addition. The Zn content in the VPO catalyst due to the presence of ZnO and possibly other Zn compounds must be between 0.2% and 10% by weight, preferably between 0.5% and 7% by weight, more preferably between 1% and 5% by weight, of Zn, respectively, relative to the total weight of the VPO catalyst.
[0041] The VPO catalyst preferably has the following elemental composition:
[0042] - 0.5 to 7 wt.% Zn,
[0043] - 0 to 0.7 wt. % Mo,
[0044] - 26 to 31 wt. % of V,
[0045] - 17 to 21 wt.% P,
[0046] - 3 to 5 wt% C,
[0047] - the balance of oxygen, respectively relative to the total weight of the VPO catalyst.
[0048] The VPO catalyst of the invention has Zn mainly as ZnO, and if the content of the ZnO phase is sufficiently high, the catalyst has reflections typical for the ZnO phase in the XRD powder diffraction pattern recorded using Cu-Kα radiation. In particular, clear reflections at 31.7° to 31.9°, 34.3° to 34.5°, 36.2° to 36.4° are detected.
[0049] According to the invention, ZnO stabilizes the catalyst particles, giving them a higher mechanical strength than would be the case in the absence of this compound. ZnO is preferably used to stabilize the VPO catalyst in particle form.
[0050] The VPO catalyst of the invention is present as a shaped body, the shape of which can be designed differently depending on the desired contact time, flow rate and dynamic pressure during the catalytic conversion. A VPO catalyst in the form of a shaped body is understood to be a shaped body prepared by a shaping step such as tableting. In a tube bundle reactor, a plurality of shaped bodies of the invention form a layer or catalyst bed, through which the reactants butane, in particular n-butane, and air are guided.
[0051] According to the invention, the shaped body should have minimum dimensions, for example the shaped body should not fit into an imaginary cube of 3 mm x 3 mm x 3 mm without exceeding its limits at one point.
[0052] For example, the shaped body of the present invention can be present in a common cylindrical shape. The cylinder then has a height of 3 mm to 8 mm (length along the axis of the cylinder) and a substantially circular bottom surface of 3 mm to 8 mm in diameter. The cylinder preferably has a central axial opening, which can have a diameter of 1 mm to 3 mm, for example.
[0053] The shaped body according to the invention may, for example, have a height of 4.7 mm, an outer diameter of 4.7 mm and a central axial opening of 1.3 mm in diameter. Such a shaped body would then have a 1.2 cm 2 The geometric surface area, 0.075 cm 3 When a plurality of such shaped bodies were loaded into a 21 mm reactor, about 0.85 g / cm 3 Up to 0.89g / cm 3 The packing density.
[0054] The shaped bodies according to the invention may have, for example, a height of 5.6 mm, an outer diameter of 5.5 mm and a central axial opening of 2.3 mm in diameter. These shaped bodies then have a 1.77 cm 2 The geometric surface area, 0.111 cm 3 When a plurality of such shaped bodies were loaded into a 21 mm reactor, about 0.72 g / cm3 Up to 0.76g / cm 3 The packing density.
[0055] Preferred shaped bodies for the reactor concept of the invention are those described in EP 2643086 A1. Preferred double alpha shapes are characterized in particular in that each individual shaped body is formed with an outer base [1], a cylindrical surface [2], a cylinder axis and at least one continuous opening [3] extending parallel to the cylinder axis, and the outer base [1] of the cylinder has at least four lobes [4a, 4b, 4c, 4d], wherein the geometrical base surrounding the shaped body is a prism with a prismatic base having a length and a width, wherein the length is greater than the width and wherein the lobes [4a, 4b, 4c, 4d] are enclosed by the prism corners of the prism base ( Figure 6 ).
[0056] Preference is given to shaped bodies in a double alpha shape having a height (length along the cylinder axis) of 3 mm to 8 mm, a length of 5 mm to 9 mm and a width of 4 mm to 8 mm and an inner pore diameter of 1 mm to 4 mm. For example, preference is given to shaped bodies in a double alpha shape having a height of 5.6 mm, a length of 6.7 mm, a width of 5.8 mm and an inner pore diameter of 2.1 mm. These catalyst shaped bodies have a diameter of 2.37 cm 2 The geometric surface area, 0.154 cm 3 When loaded into a 21 mm reactor, about 0.60 g cm 3 / to 0.62g / cm 3 The packing density.
[0057] The VPO catalyst or shaped body of the present invention has a side pressure strength of greater than 25 N, preferably between 25 N and 200 N. Particularly preferred is a side pressure strength of greater than 30 N to 150 N, more preferably greater than 35 N to 100 N.
[0058] The VPO catalyst or shaped body of the present invention in a columnar shape has a side pressure strength of greater than 25 N, preferably between 25 N and 50 N. Particularly preferred is a side pressure strength of greater than 30 N to 45 N, more preferably greater than 35 N to 40 N.
[0059] The VPO catalyst or shaped body of the present invention in double alpha shape has a side compression strength of more than 50 N, preferably between 50 N and 200 N. Particularly preferred is a side compression strength of more than 100 N to 170 N, more preferably more than 120 N to 150 N.
[0060] The invention further relates to a process for preparing the VPO catalyst according to the invention in the form of shaped bodies, comprising the following steps:
[0061] a) providing a reaction mixture comprising a V(V) compound, a P(V) compound, optionally a Mo compound, a reducing agent and a solvent,
[0062] b) reducing said V(V) compound at least partially to vanadium hydrogen phosphate with said reducing agent so as to obtain an intermediate product suspension,
[0063] c) filtering the intermediate product suspension from step b) in order to obtain an intermediate product,
[0064] d) drying and / or calcining the intermediate product at a temperature of up to 300° C. in order to obtain a dried intermediate product,
[0065] d1) optionally mixing the dried intermediate product with graphite and / or
[0066] d2) compacting or granulating the dried intermediate product,
[0067] e) forming the dried intermediate product from step d) or d1) and / or d2) into shaped bodies,
[0068] f) activating the shaped body at a temperature above 200° C. in a gas mixture of nitrogen, hydrogen and water vapor,
[0069] Characterized in that ZnO is added after step c) but before step f).
[0070] In method step a), the initial materials for reduction step b) are provided in the reaction mixture for reduction. According to the present invention, the reaction mixture comprises a V(V) compound, a P(V) compound, optionally a Mo compound, a reducing agent and a solvent as initial materials, and preferably the reaction mixture consists of these initial materials. For example, the reaction mixture can consist of 45% to 90% by weight of a solvent, 5% to 15% by weight of a reducing agent, 5% to 15% by weight of a V(V) compound, up to 1% by weight of a Mo compound and 5% to 25% by weight of a P(V) compound. Specifically, relative to the total weight of the reaction mixture, for example, 60% to 70% by weight of isobutanol, 5% to 15% by weight of benzyl alcohol, 5% to 15% by weight of vanadium pentoxide, 0.05% to 0.2% by weight of (NH 4 ) 2 MoO 4 and 10 to 20 wt % phosphoric acid.
[0071] The V(V) compound used as starting material in the reaction mixture according to step a) is a compound containing vanadium with an oxidation value of V and is preferably V 2 O 5 .
[0072] The P(V) compound used as starting material in the reaction mixture according to step a) is a compound containing phosphorus of oxidation value V and is preferably phosphoric acid or a phosphate such as Na 3 PO 4 The phosphoric acid (H 3 PO 4 ) is preferably anhydrous (100% phosphoric acid) or phosphoric acid which contains only a small amount of water, that is to say a phosphoric acid with a concentration of 98% to 100%, preferably 99% to 100% (the percentage values relate to the usually given percentage weight ratio of pure phosphoric acid to the weight of a water-phosphoric acid mixture). Alternatively, when preparing the reaction mixture according to step a), more than 100% phosphoric acid can be used, which immediately reacts with the water actually present in the reaction mixture according to step a) to give phosphoric acid with a concentration of 98% to 100%, preferably 99% to 100%, preferably 100%, so that preferably no phosphoric acid with a concentration of more than 100% is present in the reaction mixture according to step a) and at the same time no water of more than 0.2% by weight, relative to the weight of the reaction mixture, is present in the reaction mixture.
[0073] Molybdenum compounds which can optionally be used as starting materials in the reaction mixture according to step a) are any desired molybdenum-containing compounds, for example molybdenum trioxide, ammonium heptamolybdate ((NH 4 ) 6 Mo 7 O 24 )*4H 2 O), ammonium paramolybdate ((NH 4 ) 6 Mo 7 O 2 *4H 2 O), metamolybdate, molybdic acid (H 2 MoO 4 ) and its salts such as (NH 4 ) 2 MoO 4 、Na 2 MoO 4 , K 2 MoO 4 or (NH 4 ) 2 Mo 2 O 7 .
[0074] The reducing agent present in the reaction mixture according to step a) may be any desired reducing agent capable of reducing the V(V) compound to at least partially produce vanadium hydrogen phosphate. The reducing agent is preferably an organic reducing agent such as ethanol, isobutanol or an aromatic alcohol, among which benzyl alcohol is especially preferred.
[0075] The solvent present in the reaction mixture according to step a) is preferably an alcohol, particularly preferably a high-boiling aliphatic alcohol, in particular isobutanol, alternatively ethanol or isopropanol.
[0076] The starting materials are provided in a suitable reaction vessel which is capable of carrying out the subsequent reduction step b), that is to say of heating the reaction mixture to a temperature above room temperature, for example up to 100° C. After the reduction has been carried out, preferably with stirring in a reflux step, the reaction vessel preferably has a reflux cooler and a device for stirring the reaction mixture. Optionally, the reaction vessel is equipped with a device which allows the water produced during the reduction to be removed from the reaction mixture, that is to say a water separator, for example a Dean Stark water separator.
[0077] In method step b), at least partial reduction of the V(V) compound to an intermediate product is carried out, which contains a vanadium hydrogen phosphate phase and optionally molybdenum and forms an intermediate product suspension together with a solvent and the remaining components of the partial conversion from step a). This reduction is preferably carried out under reflux at normal pressure, the temperature being increased depending on the boiling point of the solvent used, preferably only a single reflux step being carried out in the method of the invention. The intermediate product preferably contains vanadium hydrogen phosphate as the main phase or can even consist essentially of a vanadium hydrogen phosphate phase. The molybdenum that may also be present in the intermediate product can be present as a dopant of the vanadium hydrogen phosphate phase, wherein a molybdenum dopant is understood to mean that molybdenum is either inserted into the vanadium hydrogen phosphate phase or is present on its surface. However, in addition to the vanadium hydrogen phosphate phase, other vanadium-phosphorus mixed oxides can also be produced during the reduction, wherein the vanadium has an oxidation valence of IV or even III. The reduction does not have to be carried out completely, so that a certain proportion of V(V) compounds and P(V) compounds remain in the intermediate product and therefore in the intermediate product suspension. However, the reduced intermediate product typically has an average vanadium oxidation valence of 3.8 to 4.2.
[0078] The water produced during the reduction can be removed from the reaction mixture during the reduction. In the prior art, the removal of water during the reduction is either done physically, for example by means of a water separator, or chemically by using compounds that bind water, that is to say, for example, drying agents or anhydrides such as phosphoric acid with a concentration of more than 100%. The reaction mixture according to step a) can, for example, have an anhydride that reacts with water and binds water, and the reaction mixture according to step a) can in particular have phosphoric acid with a concentration of more than 100%.
[0079] Method step c), that is to say the filtration of the intermediate product suspension, can be carried out, for example, in an inert gas atmosphere such as nitrogen or a rare gas. In this context, an inert gas is any gas which, under given conditions, does not react with the intermediate product during filtration but at the same time replaces oxygen from the air, thereby minimizing the risk of explosion. The filtration is carried out by means known to the person skilled in the art, typically by means of a filter press, a decanter or by means of a filter funnel. Method step c) gives an uncalcined intermediate product which is still wetted with the solvent.
[0080] The drying of the intermediate product obtained by filtration in process step d) (solid filter residue) is carried out at a temperature above room temperature, typically at a temperature of up to 150° C., under reduced pressure or vacuum or under an inert gas, in order to obtain a dried intermediate product (dried intermediate product from step d)). In this context, an inert gas is understood to mean any gas, such as nitrogen or a noble gas, which does not react with the intermediate product under drying conditions but at the same time replaces oxygen from the air and thus minimizes the risk of explosion. Drying is preferably carried out under reduced pressure or vacuum at between 50° C. and 150° C., preferably between 90° C. and 140° C.
[0081] Alternatively or optionally after drying, calcination can be carried out according to step d). Calcination is carried out under an inert gas at an elevated temperature between 150° C. and 350° C., preferably between 230° C. and 290° C. In this context, an inert gas is understood to mean any gas, such as nitrogen or a noble gas, which does not react with the intermediate product under the calcination conditions but at the same time replaces oxygen from the air and thereby minimizes the risk of explosion.
[0082] Optionally, one or more method steps d 1 ) and / or d 2 ) may be followed by method step d): according to optional method step d) 1 ) 1 to 10 wt % of graphite is mixed into the dried intermediate product to obtain an intermediate product mixture (from step d 1 ) of the dried intermediate product). According to optional process step d 2 ) will come from step d) or d 1 ) is compacted and / or granulated to obtain a compacted or granulated dried intermediate product (from step d 2 The dried intermediate product from step d) or d1) is compacted to form a sheet, for example using a roller compactor at a pressing force of 190 bar, a gap width of 0.60 mm and a roller speed of 7 rpm and granulated through a 1 mm sieve.
[0083] In method step e), the 1 ) or d2 ) is shaped into a catalyst shaped body through drying the intermediate product, which can be carried out, for example, by tableting. Here, for example, the granules are pressed into the desired tablet shape with corresponding size with a circular orbit tablet press.
[0084] In the subsequent method step f), the activation of the obtained catalyst shaped body is carried out at a temperature of more than 200° C. The activation is typically carried out in a gas mixture consisting of air, inert gas and water vapor, wherein any gas which does not react with the catalyst shaped body during activation under the given conditions can be used as inert gas, inert gas being in particular nitrogen or a noble gas. Alternatively, the activation can be carried out in a process gas, that is to say in a gas mixture comprising air and butane. The activation is carried out at a temperature in the range of 300° C. to 500° C., preferably in the range of 350° C. to 450° C. The finished VPO catalyst is obtained as a product of the method by activation. If the graphite-containing intermediate product mixture from step d1) or d2) which is deformed into a shaped body in method step e) is activated, a graphite-containing VPO catalyst is obtained as a product of the method. The tableted final product typically has a lateral compression strength of more than 25N, typically between 25N and 200N.
[0085] The method according to the invention for preparing a VPO catalyst in the form of a shaped body is characterized in that ZnO (zinc(II) oxide) is added after method step c) but before method step f), wherein the ZnO is preferably added in the form of a powdered solid. The ZnO can also be added as part of a binder having other components, which in a preferred embodiment comprises one or more other metal compounds in addition to ZnO. Preferably, the binder comprising ZnO also comprises a solid Mg compound, such as MgO.
[0086] ZnO or a binder containing ZnO is preferably added in powder form, but it is also possible to add the binder containing ZnO in liquid form, for example as a suspension. In the simplest case, the ZnO particles or ZnO crystallites are present in the form of a suspension that is insoluble in a liquid medium, such as water. However, it is also possible that the binder containing ZnO has an organic component.
[0087] The addition of ZnO or a binder containing ZnO is carried out in a suitable manner, for example by mixing a powdered binder with the intermediate product or a shaped body from the corresponding method step. This can also be carried out with the aid of a dosing device and a mixer. In general, sufficient ZnO or a binder containing ZnO is added to form a catalyst according to the invention. For example, 0.5% to 7% by weight, preferably 1% to 5% by weight, more preferably 2% to 4% by weight of ZnO can be added, relative to the weight of the dried intermediate product (without ZnO) from step d), d1) or d2).
[0088] The invention further relates to the use of ZnO in solid form for stabilizing VPO catalysts in the form of shaped bodies and to the use of ZnO as a binder for VPO catalysts in the form of shaped bodies.
[0089] As described in the present invention, ZnO can be used as a binder for the VPO catalyst and thus improve the mechanical stability of the VPO catalyst in the form of a shaped body. Preferably, when used, ZnO is mixed in powder form between steps c) to f) in the preparation method described in the present invention, that is, after step c) but before carrying out step f), or preferably between steps c) to e) or during steps c), d) or e).
[0090] The invention furthermore relates to a process for preparing maleic anhydride by catalytic oxidation of n-butane, in which a reactant gas comprising oxygen and n-butane is conducted through a reactor tube in which the VPO catalyst according to the invention is in bulk form.
[0091] The bulk form of the VPO catalyst in the reactor tube consists of the VPO catalyst or shaped body of the invention which is introduced into the reactor tube and produced in bulk form due to the flattening. The reactor tube is preferably part of a plurality of reactor tubes of a tube bundle reactor, as known to those skilled in the art for the industrial preparation of maleic anhydride. During the reaction, the bulk form of the VPO catalyst is present at a temperature between 300° C. and 420° C. The reactant gas can, for example, contain between 0.2% and 10% by volume of n-butane and between 5% and 50% by volume of oxygen and is heated at 1100 h. -1 Up to 2500h -1 , preferably 1300h -1 To 2000h -1 is directed through the reactor tube at a space-time velocity of . BRIEF DESCRIPTION OF THE DRAWINGS
[0092] Figure 1 : Effect of using ZnO or ZnO / MgO solids in the synthesis on the stability of VPO catalysts (Examples 1 to 7).
[0093] Figure 2 : Changes in lateral pressure strength and selectivity of VPO catalysts under different Zn addition amounts.
[0094] Figure 3 : XRD diffraction patterns of the VPO catalysts according to Examples 1 to 5.
[0095] Figure 4 : XRD diffraction patterns of VPO catalysts with 2 wt% ZnO added a) at the beginning of the reflux step, b) after filtration and before vacuum drying, c) after vacuum drying and before calcination, d) after calcination and before tableting (according to Examples 8 to 10 and 5, respectively).
[0096] Figure 5 : XRD diffraction patterns of a) VPO catalysts according to Example 11, b) according to Example 12 and c) according to Example 5.
[0097] Figure 6 : Views of the preferred catalyst particle, the "double alpha shape" from four different angles. Example
[0098] Example 1 (comparative)
[0099] Instruments used
[0100] A mushroom-shaped heater is arranged on the laboratory jacket and a 2-liter four-necked flask is located therein. In the middle opening of the four-necked flask there is a half-moon-shaped stirrer with a matching stirring plug, which is connected to the stirrer by means of a stirring joint. In the right opening there is a thermometer and in the left opening there is a riser pipe leading to the reflux cooler. The opening in the middle front is used for filling with chemicals, and a nitrogen flushing device is then connected there. The entire device can also be flushed with nitrogen. For this purpose, the nitrogen is first guided through a wash bottle and then introduced into the device and discharged again through the wash bottle from above the cooler.
[0101] Preparation and reduction of the reaction mixture (process steps a) and b))
[0102] First, add 1069.5 g of isobutyl alcohol and 156.0 g of benzyl alcohol. Then add 150 g of V 2 O 5 . After adding V 2 O 5 2.52 g of ammonium dimolybdate was then added. 232.50 g of phosphoric acid (100% or anhydrous) was then added to the suspension and 2 Heat at reflux for 10 hours.
[0103] Filtration (method step c))
[0104] After the intermediate product suspension has cooled, it is transferred from the four-necked flask to a filter funnel and the liquid is sucked off. The moist filter cake is dry pressed in a press at 14 to 18 bar overnight.
[0105] Drying / calcination (process step d)):
[0106] The pressed filter cake was filled into the evaporator flask of a rotary evaporator. The filter cake was dried overnight at 110° C. under a water jet vacuum. The powder thus dried was placed in an oven in a suitable calcining pan and heated at a temperature of 200 to 300° C. under N 2 Calcination in atmosphere for 9 hours.
[0107] Compacting / tabletting (method step d 1 ,d 2 and e)):
[0108] Before compacting / tabletting, 5% by weight of graphite was added to the calcined powdery intermediate product and mixed uniformly with the aid of a drum hoop mixer. This powder was compacted into plates using a roller compactor at a pressing force of 190 bar, a gap width of 0.60 mm and a roller speed of 7 rpm and granulated through a 1 mm sieve.
[0109] The granules are compressed into the desired tablets with corresponding size, eg, 5.6 x 5.6 x 2.3 mm, and side compression strength using a circular orbital tablet press.
[0110] Activation to pyrophosphate (method step f)):
[0111] The activation process to produce vanadium pyrophosphate is carried out under controlled conditions in a retort installed in a programmable oven. The calcined sheets are uniformly filled into the retort and sealed. The catalyst is then activated in a moist air-nitrogen mixture (50% air humidity) first at above 300° C. for 5 hours and then at above 400° C. for 9 hours.
[0112] Examples 2 to 7 (according to the present invention)
[0113] The VPO catalyst according to the invention was prepared analogously to Example 1, with the difference that per 100 g of calcined powder from process step d) there were 4.5 g (Example 2), 1.8 g (Example 3), 5.0 g (Example 4), 2.0 g (Example 5), 1.0 g (Example 6), 0.5 g (Example 7) of ZnO powder (commercial ZnO, particle size <100 μm, impurities less than 0.05% by weight) and 0.5 g (Example 2) and 0.2 g (Example 3) of MgO powder, and graphite was mixed in. This gave calcined precursor powders with 5.0% by weight of ZnO / MgO (Example 2), 2.0% by weight of ZnO / MgO (Example 3), 5.0% by weight of ZnO (Example 4), 2.0% by weight of ZnO (Example 5), 1.0% by weight of ZnO (Example 6), 0.5% by weight of ZnO (Example 7).
[0114] The VPO catalysts according to Examples 1 to 7 were tested for their breaking strength before and after activation (process step f)). Furthermore, the XRD diffractograms of the VPO catalysts were determined and their catalytic selectivity was tested.
[0115] In Table 1 and Figure 1 The results presented in show that by adding ZnO or ZnO / MgO after the calcination step, no systematic increase in the lateral compressive strength (SCS) can be observed when measured directly after tableting. However, unexpectedly an increase is observed after the subsequent step of activating the VPO catalyst tablets. A systematic and very significant increase in the lateral compressive strength of the particles to which ZnO or ZnO / MgO was added is shown here.
[0116] Besides the increase in mechanical strength, even with this addition the catalytic properties achieved are decisive. Figure 2 The results of the catalytic test reactions in WO 2009 / 052735 show that the stabilized shaped catalyst bodies according to the invention have useful catalytic properties.
[0117] exist Figure 3 The XRD diffraction pattern in shows that the following features appear by adding ZnO:
[0118] 31.7° to 31.9° (clear reflection, ZnO)
[0119] 34.3° to 34.5° (clear reflection, ZnO)
[0120] 36.2° to 36.4° (clear reflection, ZnO)
[0121] These features become stronger with increasing ZnO content and are in good agreement with ZnO (either in the wurtzite structure or as zincite).
[0122] Comparative Example 8, Examples 9 and 10
[0123] In order to examine the relationship between the presence of the stabilizing ZnO phase and the time of addition of the binder, XRD diffractograms were recorded after different addition times. In Examples 2 to 7, ZnO was always added after calcination and before tableting, while during process step a), the ZnO was added at the time of preparation of the reaction mixture, i.e. at the time of addition of the V 2 O 5 ZnO was added together (Comparative Example 8), directly after the filtration in process step c) (Example 9), during process step d), that is, after vacuum drying and before calcination (Example 10). In each case, 5.2 g of ZnO were added, so that the finished catalysts contained nominally 2% by weight of ZnO.
[0124] Figure 4 It is shown that when ZnO is added at the beginning of the reflux step, the XRD reflections observed when ZnO is added after calcination and before tableting are not seen, especially at 31.7 to 31.9°, 34.3 to 34.5°, 36.2 to 36.4°. Figure 4 , corresponding to the diffraction pattern a) of Comparative Example 8.
[0125] Comparative Examples 11 and 12
[0126] The VPO catalysts according to Comparative Examples 11 and 12 were prepared analogously to the VPO catalyst according to Example 1, wherein Zn(OAc) 2 The activated sheets were impregnated with the solution. Two different concentrations were used in order to obtain a Zn / V ratio of 0.008 (=0.29 wt. % Zn relative to the total weight of the catalyst) or 0.016 (corresponding to 0.58 wt. % relative to the total weight of the catalyst). After impregnation, the catalyst was first dried in air at 100° C. for 18 hours and then at 350° C. for 20 minutes.
[0127] Figure 5 The XRD diffraction patterns of the VPO catalysts according to Comparative Examples 11 and 12 are shown, compared to the VPO catalyst prepared according to the present invention according to Example 5. It can be seen that by adding the ZnO compound to the activated flakes, no reflections, especially reflections at 31.7 to 31.9°, 34.3 to 34.5°, 36.2 to 36.4° are shown.
[0128] Comparative Examples 13 and 13a
[0129] The VPO catalyst according to comparative example 13 was prepared analogously to the VPO catalyst according to example 2, wherein 10% by weight of a binder of the SECAR 71 type and 4% by weight of graphite were added to the calcined powder.
[0130] The stability of the VPO catalyst can be particularly well tested by measuring the stability with respect to the by-product water, since during the reaction a large amount of water vapor is present due to the oxidation reaction, which can damage the catalyst. Therefore, the stability of the VPO catalyst according to the invention according to Example 4 with respect to the by-product water was tested in comparison with the VPO catalyst prepared with a conventional binder according to Comparative Example 13. In addition, the selectivity of the untreated sample was tested, and then the two samples were impregnated with water and the selectivity test was repeated (Comparative Example 13a). This shows that the catalyst according to the invention does not suffer a selectivity loss within the measurement tolerance range due to immersion in water.
[0131] Examples 14 and 15
[0132] The VPO catalysts according to Examples 14 and 15 were prepared analogously to the VPO catalyst according to Example 1, but without the addition of ammonium dimolybdate, so that the obtained VPO catalysts contained no Mo.
[0133] In addition, 1 wt% (Example 14) or 2 wt% (Example 15) of ZnO relative to the total weight of the calcined powder was added to the calcined powder after calcination and before tableting. As shown in Table 1, an improvement in side compression strength was achieved even in the VPO catalyst containing no Mo.
[0134] Example 16 (Comparative)
[0135] Instruments used
[0136] The same apparatus as in Example 1 was used.
[0137] Preparation and reduction of the reaction mixture (process steps a) and b))
[0138] First, 150g of V 2 O 5 Place in a four-necked flask in advance. Add 300 mL of benzyl alcohol and 1200 mL of isobutyl alcohol. 2 After inertization, the suspension was heated to reflux with stirring for 10 hours. After cooling to a maximum of 40° C. with stirring, 7.51 g of ammonium dimolybdate, 6.60 g of iron(III) nitrate nonahydrate, 2.55 g of cerium(III) nitrate hexahydrate and 4.5 g of ammonium niobium oxalate were added. 138 ml of phosphoric acid (85%) were added within 15 minutes with stirring and the mixture was heated with N 2After inertization, the suspension was heated again at reflux with stirring for 24 hours.
[0139] Filtration (method step c))
[0140] After the intermediate product suspension has cooled, it is transferred from the four-necked flask to a filter funnel and the liquid is aspirated off. The wet filter cake is washed once with ethanol (100%) and the liquid is aspirated off again in the filter funnel. The same procedure is then repeated with double distilled water.
[0141] Drying / calcination (process step d)):
[0142] The washed filter cake was filled into the evaporator flask of a rotary evaporator. The filter cake was dried overnight at 120° C. under a water jet vacuum. The powder thus dried was placed in an oven in a suitable calcining pan and heated at a temperature of 200 to 300° C. under N 2 Calcination in atmosphere for 9 hours.
[0143] Compacting / tabletting (method step d 1 ,d 2 and e)):
[0144] 2.1 wt.% Zn was first added to the calcined powdered intermediate product before compaction / tabletting. 3 (PO 4 ) 2 4% by weight of graphite was then added and mixed homogeneously by means of a drum hoop mixer. This powder was compacted to a plate using a roller compactor at a pressing force of 190 bar, a gap width of 0.60 mm and a roller speed of 7 rpm and granulated through a 1 mm sieve.
[0145] The granules are compressed into the desired tablets with corresponding size, eg, 5.6 x 5.6 x 2.3 mm, and side compression strength using a circular orbital tablet press.
[0146] Temperature treatment:
[0147] The following temperature treatment was carried out under controlled conditions in a retort installed in a programmable oven. The calcined pieces were uniformly packed into the retort and it was sealed. The catalyst was then treated in an air stream at 120° C. for 18 hours.
[0148] Example 17 (Comparative)
[0149] The VPO catalyst according to Example 17 was formed analogously to the VPO catalyst according to Example 1, wherein 2.1 wt. % Zn relative to the total weight of the calcined powder was added to the calcined powder after calcination and before tableting. 3 (PO 4 ) 2 .
[0150] Table 1: Summary of results
[0151]
[0152] method
[0153] Breaking strength test
[0154] Use Zwick Z0.5 equipment to measure the fracture strength of the formed body in order to determine the force required for fracture. The measurement is carried out according to the ASTM D4179 standard. In order to dry the formed body before measurement, it is stored in a drying oven at 100 ° C for at least 3 hours and the subsequent fracture strength measurement is carried out within a maximum of 1 hour after the drying is completed. According to the ASTMD4179 standard, the equipment is operated at a constant force rate of 20.0N / s. For each embodiment, 100 pieces are placed in a manner parallel to the measurement baking surface with the cylinder axis in succession (ASTM D4179 standard of "radial crushing (RADIAL CRUSH)") and measured. Then, the average value is determined from 100 individual values of the force required for the fracture of the formed body, which corresponds to the average fracture force of the formed body. All numerical values about the lateral compression strength in this application relate to the lateral compression strength obtained by the method described herein.
[0155] Powder X-ray Diffraction (XRD)
[0156] The catalysts are characterized by means of X-ray powder diffraction (XRD). In this process, X-ray radiation is diffracted at different diffraction angles at crystalline regions of the sample. The diffraction angles are measured or recorded in 2θ. In this process, characteristic reflections occur depending on the diffraction angle, depending on the phase present. With the help of these diffraction patterns, the diffraction patterns can be assigned to the phases present using a database.
[0157] The measurements were carried out on a Bruker AXS D4 Endeavor with Cu-Kα radiation and LYNXEYE detector. The diffraction patterns were recorded in a 2θ angular range of 5° to 50° with a step size of 0.02° at a recording time of 1.5 s per step with a fixed divergence slit of 0.3°. For the measurements, the samples were finely ground and pressed into a sample holder. A change in the diffraction angle can be achieved in the device by turning the sample over. All numerical values in this application concerning XRD reflections relate to the XRD reflections obtained in this way.
[0158] For better comparability of diffraction patterns, they are normalized respectively. For this reason, for each diffraction pattern, first find the data point with the minimum intensity value. Extract this value from all intensity values of the corresponding diffraction pattern. Then obtain the maximum intensity (at 28.4-28.5 ° 2θ value) of the (024) reflection in the corresponding diffraction pattern. Divide all intensity values of the corresponding diffraction pattern by this value.
[0159] Catalytic test reaction
[0160] To obtain the catalyst performance, all catalysts after the complete preparation (reflux, filtration, vacuum drying, calcination, compaction, tableting, activation) were tested for their catalytic properties in a "Bench-Scale" reactor in 1.5 mol% butane in air in a diluted catalyst bed (1:9 catalyst mixture: ceramic inert rings). The selectivity to maleic anhydride (MA) was obtained from the experimental data at a mass-related GHSV of 5500 l / kg / h.
Claims
1. A VPO catalyst in the form of a shaped body for the oxidation of hydrocarbons with molecular oxygen, in particular for the oxidation of butane with molecular oxygen to maleic anhydride, characterized in that The VPO catalyst comprises ZnO.
2. The VPO catalyst according to claim 1, characterized in that The shaped body has a lateral compression strength greater than 25N, preferably between 25N and 200N, wherein the lateral compression strength is measured using the Zwick Z0.5 device at a constant force rate of 20.0N / s according to the ASTM D4179 standard, wherein 100 pieces are individually placed with the cylinder axis parallel to the measurement baking surface and measured to determine the average breaking force, which is the lateral compression strength.
3. The VPO catalyst according to claim 1 or 2, characterized in that When the VPO catalyst was studied by powder X-ray diffraction, the VPO catalyst had reflections at 31.7° to 31.9°, 34.3° to 34.5° and 36.2° to 36.4° when measured with a D4 Endeavor of a Bruker AXS with Cu-Kα radiation and a LYNXEYE detector, wherein the diffraction pattern was recorded in the 2θ angle range of 5° to 50° with a step size of 0.02° at a recording time of 1.5 s per step with a fixed divergence slit of 0.3°.
4. The VPO catalyst according to any one of the preceding claims, characterized in that The VPO catalyst comprises a Mo content of between 0.1 wt.-% and 1 wt.-%, preferably between 0.4 wt.-% and 0.7 wt.-% Mo, respectively, relative to the total weight of the VPO catalyst.
5. The VPO catalyst according to any one of the preceding claims, characterized in that The VPO catalyst comprises between 0.2 and 10 wt.-%, preferably between 0.5 and 7 wt.-%, more preferably between 1 and 5 wt.-% Zn, relative to the total weight of the VPO catalyst.
6. The VPO catalyst according to any one of the preceding claims, characterized in that The VPO catalyst has the following elemental composition: - 0.5 to 7 wt.% Zn, - 0 to 0.7 wt. % Mo, - 26 to 31 wt. % of V, - 17 to 21 wt.% P, - 3 to 5 wt% C, - the balance of oxygen, respectively relative to the total weight of the VPO catalyst.
7. The VPO catalyst according to any one of the preceding claims, characterized in that The formed body has a double alpha shape with a height of 3 mm to 8 mm, a length of 5 mm to 9 mm, a width of 4 mm to 8 mm, and a hole inner diameter of 1 mm to 4 mm.
8. The VPO catalyst according to any one of claims 1 to 6, characterized in that The shaped body has a cylindrical shape with a height of 3 mm to 8 mm, a substantially circular bottom surface with a diameter of 3 mm to 8 mm and a central axial opening with a diameter of 1 mm to 3 mm.
9. A method for preparing the VPO catalyst according to any one of claims 1 to 8, the method comprising the following steps: a) providing a reaction mixture comprising a V(V) compound, a P(V) compound, optionally a Mo compound, a reducing agent and a solvent, b) reducing said V(V) compound at least partially to vanadium hydrogen phosphate with said reducing agent so as to obtain an intermediate product suspension, c) filtering the intermediate product suspension from step b) in order to obtain an intermediate product, d) drying and / or calcining the intermediate product at a temperature of up to 300° C. in order to obtain a dried intermediate product, d1) optionally mixing the dried intermediate product with graphite and / or d2) compacting or granulating the dried intermediate product, e) forming the dried intermediate product from step d) or d1) and / or d2) into shaped bodies, f) activating the particles at a temperature above 200° C. in a gas mixture formed from an inert gas, hydrogen and water vapor, Characterized in that ZnO is added after step c) but before step f).
10. The method for preparing a VPO catalyst according to claim 9, characterized in that: In step b) the solvent is an alcohol and the reducing agent is an organic reducing agent.
11. The method for preparing a VPO catalyst according to claim 9 or 10, characterized in that: The reduction in step b) is carried out at a temperature above 40° C., preferably under reflux at atmospheric pressure.
12. The method for preparing a VPO catalyst according to any one of claims 9 to 11, characterized in that Said drying according to step d) is carried out under reduced pressure or under vacuum at between 90°C and 140°C.
13. The method for preparing a VPO catalyst according to any one of claims 9 to 12, characterized in that The added ZnO is part of a binder having other constituents.
14. The method for preparing a VPO catalyst according to claim 13, characterized in that: The binder comprises a Mg compound, preferably MgO.
15. The method for preparing a VPO catalyst according to any one of claims 9 to 14, characterized in that The activation step is carried out in a gas mixture consisting of air, inert gas and water vapor at a temperature in the range of 300° C. to 500° C., preferably in the range of 350° C. to 450° C., during a period of 1 hour to 24 hours.
16. The method for preparing a VPO catalyst according to claim 15, characterized in that: The inert gas is nitrogen or a rare gas.
17. The method for preparing a VPO catalyst according to any one of claims 9 to 16, characterized in that Step d) is divided into two steps d i ) and d ii ) is performed, wherein in step d i ) is dried under reduced pressure at between 90° C. and 140° C., and in step d ii ) during calcination in nitrogen at between 230°C and 290°C.
18. The method for preparing a VPO catalyst according to claim 17, characterized in that: Step d i ) is carried out during a period of time between 5 hours and 48 hours, and step d ii ) is performed during a time period between 5 hours and 24 hours.
19. The method for preparing a VPO catalyst according to any one of claims 9 to 18, characterized in that The activation of the VHP phase is carried out in two consecutive steps f1) and f2), wherein during step f1) the catalyst is activated at a temperature ranging from 250° C. to 350° C. during a period of time between 1 hour and 8 hours, and during step f2) the catalyst is activated at a temperature ranging from 350° C. to 450° C. during a period of time between 4 hours and 20 hours.
20. Use of ZnO for stabilizing VPO catalysts in particle form.
21. The use according to claim 20, wherein the VPO catalyst is prepared in the form of shaped bodies according to the process according to claims 9 to 19.
22. Use of ZnO as a binder for VPO catalysts in the form of shaped bodies.
23. A process for preparing maleic anhydride by catalytic oxidation of n-butane, wherein reactant gases comprising oxygen and n-butane are conducted through a reactor tube in which the VPO catalyst according to any one of claims 1 to 8 is in bulk form.
24. The method according to claim 23, characterized in that The VPO catalyst in bulk form in the reactor tube is present at a temperature between 300°C and 420°C.
25. The method according to any one of claims 23 or 24, characterized in that The reactant gas comprises between 0.2% and 10% by volume of n-butane and between 5% and 50% by volume of oxygen and is heated at 1100 h -1 Until 1800h -1 , preferably 1300h -1 Up to 2500h -1 A space-time velocity of is directed through the reactor tube.
Citation Information
Patent Citations
Method of regenerating maleic anhydride produced from n-butane fluidized-bed catalyst
CN101036891A
Preparation method of vanadium phosphorus oxide catalyst
CN106938197A
Method for preparing hydrotalcite-assisted vanadium-phosphorus-oxygen catalyst
CN111701608A
Alkali metal-modified vanadium phosphorus oxide (VPO) catalyst
DE102014004786A1
Catalyst shaped body for flow-conducting fixed-bed reactors
EP2643086A1